Role of Quality Management System (QMS) for Effective Regulatory Compliance - Kulkarni, Bhavani; Chandra Vemuri, Ravi (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2014)
Present day the biggest challenge faced by the pharmaceutical manufacturers is experiencing inspectional Food and Drug administration (FDA) 483’s, warning letters, import alerts and notice of violations from the regulatory authorities. The USFDA’s inspectional outcome has uncovered the retesting of drug ingredients that had failed quality testing, failure to establish corrective and preventive action following an investigation, procedural lapses etc. All these regulatory non-compliances triggered the FDA to issue warning letters, with holding of the product approval or plant shut-down because the US regulator has perceived violations to be of serious significance. Most experts warn that quality systems should focus on sustainability issues and assume that quality problems and regulatory non-compliances will be reduced as a result of the organized way of thinking, transparency, documentation and continuous evaluation of Quality Management System (QMS). QMS is a set of coordinated activities to direct and control an organization in order to continually improve the effectiveness and efficiency of its performance. It is designed and implemented to emphasize continuous improvement for state of compliance. QMS starts with recognizing that customers play a significant role in defining requirements as inputs and monitoring of customer satisfaction is necessary to evaluate and validate whether customer requirements have been met. QMS also lives in a dynamic regulatory environment of the registration and compliance requirements of global markets as well as inspections. As QMS is related to regulatory compliance and continuous inspection readiness, it shall maximize benefit to the organization by improving quality, increasing the yield, cutting costs and finally curbing FDA 483’s, warning letters and import alerts. The article details about the significance of QMS and its modules for effective regulatory compliance.
Keywords: Warning letters